Pituitary Macroadenoma with Apoplexy, a Mimicker of Normal Tension Glaucoma (NTG): A Case Report - Thinley; Vaidya, Keepa; Tamang, Sandip (Nepalese Journal of Ophthalmology, 2024)
Background: Asymmetric visual field defects with a high cup-to-disc ratio resembling glaucomatous damage can be the only clinical features of a pituitary macroadenoma with apoplexy, posing diagnostic challenges. Case: A 39-year-old man presented with a history of gradual onset, progressive visual obscuration in the right visual field for one month without any other accompanying neurological symptoms. On examination, his intraocular pressure (IOP) was 16 mmHg in both eyes. Posterior segment examination revealed a cup to-disc ratio (CDR) of 0.8 in the right and 0.7 in the left eye, with concentric neuroretinal rim thinning and mild temporal disc pallor. These findings led to the diagnosis and treatment of normal tension glaucoma (NTG) elsewhere. Visual field examination showed field defects featuring a junctional scotoma. The MRI scan of the brain revealed a well-defined mass lesion situated in the sella suggestive of pituitary macroadenoma with possible apoplexy confirmed later through histopathological examination. The neurosurgery team successfully removed the tumor through the endoscopic endonasal trans-sphenoidal approach and the patient reported significant improvement in vision and visual field defects. Observations: In our case, visual signs and symptoms were the only presenting features, caused by pituitary macroadenoma with apoplexy, which can be a potentially life-threatening condition. Although pituitary apoplexy is an acute condition with numerous neurological signs and symptoms, visual symptoms with high CDR and neuroretinal rim thinning with mild temporal disc pallor were the only features seen in our case, posing a diagnostic challenge. There were no associated systemic manifestations. However, the patient had a favorable outcome because of prompt diagnosis and multidisciplinary management. Conclusion: The spectrum of clinical manifestations of pituitary macroadenoma with apoplexy should encompass a gradual onset, progressive asymmetric visual field defect with temporal disc pallor to facilitate timely diagnosis and effective management.